European financial markets and institutions - Haan, Jakob de; Oosterloo, Sander; Schoenmaker, Dirk (Cambridge University Press, 2009)
Written for undergraduate and graduate students of finance, economics and business, this textbook provides a fresh analysis of the European financial system. Combining theory, empirical data and policy, it examines and explains financial markets, financial infrastructures, financial institutions, and challenges in the domain of financial supervision and competition policy.